The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/jcm12123949
|View full text |Cite
|
Sign up to set email alerts
|

Aortopathies: From Etiology to the Role of Arterial Stiffness

Abstract: The aorta and aortic wall have a complex biological system of structural, biochemical, biomolecular, and hemodynamic elements. Arterial stiffness could be considered a manifestation of wall structural and functional variations, and it has been revealed to have a strong connection with aortopathies and be a predictor of cardiovascular risk, especially in patients affected by hypertension, diabetes mellitus, and nephropathy. Stiffness affects the function of different organs, especially the brain, kidneys, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…There are many different mechanisms behind aortopathies, like the bicuspid aortic valve, inflammatory diseases, FMD, and heritable connective tissue disorders (e.g., Ehlers–Danlos syndrome) [ 56 , 57 ]. It has been reported that bovine arch variation is associated with the occurrence of aneurysms or type B aortic dissection [ 57 ], as well as with an early age at stroke presentation (on average, 53 years old), compared to normal branching pattern (61 years) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many different mechanisms behind aortopathies, like the bicuspid aortic valve, inflammatory diseases, FMD, and heritable connective tissue disorders (e.g., Ehlers–Danlos syndrome) [ 56 , 57 ]. It has been reported that bovine arch variation is associated with the occurrence of aneurysms or type B aortic dissection [ 57 ], as well as with an early age at stroke presentation (on average, 53 years old), compared to normal branching pattern (61 years) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, type B dissections, such as the one in our present study, often occur in patients with normal-sized or only mildly enlarged aortae, and, therefore, are unpredictable [ 46 ]. Malformative pathology of the aorta is often associated with congenital and/or valve diseases [ 56 , 57 ]. Aortic dissection and rupture are often consequences of disturbed shear stress.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, aging brings about various changes in the blood vessels, including increased arterial diameter, hypertrophy of the arterial wall, increased arterial stiffness, and endothelial dysfunction [ 12 , 13 , 14 , 15 , 16 ]. Furthermore, inflammation is described as a key mechanism in the development of atherosclerosis, with C-reactive protein (CRP), interleukins, tumor necrosis factor-alpha (TNF- ), and transforming growth factor-beta (TGF- 1) identified as risk factors [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%